2014
DOI: 10.1093/infdis/jiu057
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Management of Hepatitis C: Does Sex Play a Role?

Abstract: Hepatitis C virus infection is a disease that disproportionately affects men more than women. After initial HCV infection, women are more likely to clear the virus spontaneously. Women also have slower rates of liver disease progression than men if they become chronically infected. However, this rate of disease progression changes over time in women. Postmenopausal women have increased rates of fibrosis compared with women of reproductive age because they have lost the protective effects of estrogen. Estradiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 36 publications
13
82
2
5
Order By: Relevance
“…Women are more likely to eradicate hepatitis C virus than men after they are exposed to initial infection. However, postmenopausal women exhibit increased rates of fibrosis compared with those of reproductive age because they have lost the protective effects of oestrogen (Baden et al, 2014). The evident increase in oestrogen levels in pregnant women, especially in the third trimester, facilitates HEV infection; by contrast, HEV replication reduces ER expression.…”
Section: Discussionmentioning
confidence: 99%
“…Women are more likely to eradicate hepatitis C virus than men after they are exposed to initial infection. However, postmenopausal women exhibit increased rates of fibrosis compared with those of reproductive age because they have lost the protective effects of oestrogen (Baden et al, 2014). The evident increase in oestrogen levels in pregnant women, especially in the third trimester, facilitates HEV infection; by contrast, HEV replication reduces ER expression.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection usually disproportionately affects men more than women 43 . Apetite hormone ghrelin is reduced in chronic hepatitis C patients 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Because both male and female mice have a similar degree of reduced food intake, greater reduction of body weight in males may not be caused by gender-specific loss of apetite. Women are more likely to clear the virus spontaneously and have slower rates of liver disease progression than men if they become chronically infected 43 . Overall, both genders of mice showed similar rates of persistent infection, but liver pathology progresses slightly faster, if any, in males (Supplementary information, Table S9).…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of HCV infection varies by sex, with increased viral clearance and slower progression of liver disease in women compared with men, possibly resulting from a protective effect of estrogen on the liver. [14][15][16] Sex may also modify the response to ART among HIV-infected individuals. While some studies have found no association of sex with response to ART, [17][18][19] others have suggested that women have superior virologic, immunologic, and clinical outcomes compared with men.…”
Section: Introductionmentioning
confidence: 99%